A new Monte Carlo model of a Cyberknife® system for the precise determination of out-of-field doses. (4th October 2019) - Colnot, J; Barraux, V; Loiseau, C; Berejny, P; Batalla, A; Gschwind, R; Huet, C
Abstract: In a previous work, a PENELOPE Monte Carlo model of a Cyberknife system equipped with fixed collimator was developed and validated for in-field dose evaluation. The aim of this work is to extend it to evaluate peripheral doses and to determine the precision of the treatment planning system (TPS) Multiplan in evaluating the off-axis doses. The Cyberknife ® head model was completed with surrounding components based on manufacturer drawings. The contribution of the different head parts on the out-of-field dose was studied. To model the attenuation and the modification of particle energy caused by components not modelled, the photon transport was modified in one of the added components. The model was iteratively adjusted to fit dose profiles measured with EBT3 films and an ionization chamber for several collimator sizes. Finally, dose profiles were calculated using the two Multiplan TPS algorithms and were compared to our simulations. The contributions to out-of-field dose were identified as scattered radiation from the phantom and head leakage and scatter originating at the secondary collimator level. Particle transport in the additional pieces was modified to model this radiation. The maximum differences between simulated and measured doses are of 20.4%. Regarding the detector responses away from axis, EBT3 films and the Farmer chamber give similar response (less than 20% difference). The TPS Monte Carlo algorithm underestimates the doses away from axis more importantly for the smaller field sizes (up to 98%). Besides, RayTracing simplifies peripheral dose to a constant value with no inclusion of particle transport. A Monte Carlo model of a Cyberknife system for the determination of out-of-field doses up to 14 cm off-axis was successfully developed and validated for different depths and field sizes in comparison with measurements. This study also confirms that TPS algorithms do not model peripheral dose properly.